Clathrochelates meet phosphorus. New thio- and phosphorylation reactions of an iron(ii) dichloroclathrochelate precursor and preparation of its first phosphorus(iii)-containing macrobicyclic derivative123. Issue 12 (23rd February 2016) - Artyushin, Oleg I.; Matveeva, Ekaterina V.; Vologzhanina, Anna V.; Voloshin, Yan Z.
Abstract : (Thio)phosphorylation of an iron(ii ) dichloroclathrochelate gave P V, Cl - and P V, P V -substituted cage complexes, undergoing chemical reduction to their phosphorus(iii )-containing derivatives. Abstract : Phosphorylation reactions of an iron(ii ) dichloroclathrochelate FeBd2 (Cl2 Gm)(BF)2 (where Bd 2− and Cl2 Gm 2− are α-benzildioxime and dichloroglyoxime dianions, respectively) with diphenylphosphine oxide and diethyl thiophosphite were performed under phase-transfer conditions. In the case of diethyl thiophosphite as a P -nucleophile, the best yields were obtained in the dichloromethane–50% NaOH aqueous solution–5 mol% triethylbenzylammonium chloride (TEBAC) system. The use of different molar ratios of a macrobicycle precursor and this thiophosphorylating agent allowed us to obtain both the mono- and the diphosphorylated cage complexes. Nucleophilic substitution with diphenylphosphine oxide was performed in the K2 CO3 –acetonitrile–5 mol% TEBAC system, giving only the corresponding monophosphorylated iron(ii ) complex in high yield even in the presence of an excess of this P -nucleophile. The phosphorus(v )-containing clathrochelate product was reduced with an excess of silicoform to give an iron(ii ) macrobicycle with an inherent diphenylphosphine group in an almost quantitative yield, which was then characterized by 31 P 1 H NMR and single-crystal X-ray diffraction; it easily undergoes re-oxidation to the initial clathrochelate. The synthesized phosphorus(v )-containing cage complexes were characterized using elemental analysis, MALDI-TOF mass, IR, UV-Vis, 1 H, 11 B, 13 C 1 H, 19 F 1 H and 31 P 1 H NMR spectra, and by single-crystal X-ray diffraction.